SYNERGISM BETWEEN RHIZOSPHERE BACTERIA ISOLATES FROM Scleria sp., Clidemia sp., AND Panicum sp. TO INCREASE THE EFFECTIVENESS OF MIXED CULTURES IN HYDROCARBON BIODEGRADATION - Hardestyariki, Dwi; Yudono, Bambang; Munawar, Munawar (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2021)
The purpose of this research is to obtain hydrocarbon degrading bacteria that work synergistically in a consortium. Consortium microorganisms is mixture of microbial populations in the form of communities that have mutualistic relationships and doesnâ€™t inhibition the growth of other microbes. In this study, isolates were obtained from the rhizosphere of soil contaminated with petroleum. The isolates obtained were tested for synergism to determine the relationship between bacterial isolates. Synergism testing was carried out using the spread plate method on agar media. The results of this study showed that isolate number one showed antagonistic properties to other bacterial isolates by forming a clear zone around the disc paper. A total of eight bacterial isolates showed the greatest percentage of synergism, namely â‰¥ 80% so that the eight rhizosphere bacterial isolates could be used as materials for mixed culture.